Performing triple and quadruple figure skating jumps: Implications for training - King, D. L. (Canadian Journal of Applied Physiology, 2005)
The purpose of this paper is to review the biomechanics of triple and quadruple figure skating jumps, focusing on information that has implications for strength and conditioning programs. At a minimum, to complete the required revolutions in a jump, a skater must balance the average angular velocity with the time in the air. Vertical velocity at takeoff is similar in high revolution jumps to that in low revolution jumps; however, when comparing skaters of different abilities, those with higher abilities generate greater vertical velocities at takeoff for the same type of jump. Powerful extension of the legs is the primary factor in generating vertical velocity. Some jumps use asymmetrical extension of both legs, while other jumps involve extension of only one leg. Angular velocity is controlled primarily by the skater`s moment of inertia, which means skaters must forcefully arrest the motion of the arms and legs after the propulsion phase and then quickly position the arms and legs close to the axis of rotation during flight. Training exercises that emphasize eccentric and concentric muscle actions and which are adaptable to asymmetrical or unilateral motions, such as box jumps and medicine ball throws, are a crucial component to off-ice training programs for figure skaters.